Szociológiai válaszkísérletek a mikro-makro problémára - Tardos, Róbert (Szociológiai Szemle, 2024)
The paper aims to tackle some current issues of social research discussion raised by the micro-macro problem in recent decades. Making a distinction between several aspects of the problem such as the scope of object, the (individualistic vs. holistic) character of approach and the treatment of transition between micro and macro (or the other way), it concentrates on the former two facets (and primarily the second one). Ontological questions such as those on the priority between the micro and macro sides are ignored, on the other hand, for their sterility. After outlining a broad theoretical-historical background and presenting a tentative scheme of the micro and macro approaches in the field of sociology the study illustrates the differences by the example of the stages of career and the latest works of one of the leading contemporary macro-sociologists Peter Blau. Giving a brief overview of the basic concepts of his differentiation theory it focuses attention on the central role of emergent properties in his conceptualisation of social structure and on the twin notion of ’intersection/consolidation’ in his substantive theory of crosscutting social circles. The section on Blau is concluded by a presentation of his debate with an outstanding figure of the other camp James Coleman sharply illuminating some focal traits of the micro and macro platforms. With a reference to this debate, the paper raises the question of the sociological tenability of the basic standpoints of methodological individualism taken in a strict sense. It also argues, from a practical point of view, for a transitory differentiation of the micro and macro types of sociological theory-building. The author takes account of some recent methodological developments as well (among others the latest solutions to the ecological inference problem) that may consolidate the previously uneven empirical foundations of macro-sociological endeavours.